A review on a high performance computing-based interval fuzzy type-2 model for web services' QoS evaluation - Hasan, M.H. (Association for Computing Machinery, 2016)
Web services' QoS evaluation involves high degree of uncertainty due to the unpredictable nature of network. Existing models are not realistic because they apply crisp computation. Hence, a model using Interval Fuzzy Type-2 (IT2) method was proposed in our previous work. IT2 method was selected because it has better ability than Fuzzy Type-1 and crisp methods in handling uncertainties. However, the introduction of an extra component and a degree of freedom has made IT2 method computationally expensive. Therefore, it is proposed that the IT2-based web services' evaluation model to be implemented on high performance computing (HPC) platform. This paper reviews previous research that are related to HPC-based IT2 implementation as well as discusses the implications of the work. Â© 2016 ACM.